التكوين أثناء الخدمة وعلاقته بالأداء الوظيفي - مساعيد, نورة (University of Eloued جامعة الوادي, 2015)
إن التكوين أثناء الخدمة للموظفين يعتبر أحد الأسس والمتطلبات الضرورية لأية سياسة تتبنها المؤسسة من اجل تحسين مستوى الموظفين وتطوير قدراتهم وتنمية مهاراتهم وتعديل سلوكاتهم وتحفيزهم واستخراج أقصي ما لديهم من الطاقات وتعميق خبراتهم من أجل مسايرة ومواكبة مختلف التطورات الحاصلة على مستوى الداخلي أو على مستوى البيئة الخارجية حتى تتمكن لمؤسسة من تحسين أداء موظفيها. ولن يأتي هذا إلا بفضل ممارسة التكوين ممارسة علمية موجهة لتلبية احتياجات المؤسسة والاستجابة لخصوصياتها في ظل محيط يتسم بالتقلب و المفجاءات ولا مجال للحديث اليوم عن مدى أهمية البرامج التكوينية والقيام بالأفعال ، ومن ثمة تحقيق التنمية الشاملة والمستدامة. ث Abstract: The configuration during the service staff is considered one of the essential foundations and requirements of any policy organization Taatpinha in order to improve the level of staff and develop their abilities and develop their skills and modify their behaviors and motivate them and extract the maximum of their energies and deepen their expertise in order to keep pace and keep up with the various developments on the domestic level, or developments in the external environment level until be able to improve the performance of enterprise employees. This will not only come thanks to the practice configuration geared to meet the needs of the institution and to respond to privacy under the environment of volatile and Mufjaouat no room to talk today about how important formative programs and do deeds, and from there to achieve comprehensive and sustainable development in a scientific exercise.
تخصص علم نفس